Analisis Yuridis Putusan No.87/Pdt.G/2020 PN.Bdg Tentang Perceraian yang disebabkan Salah Satu Pihak Pindah Agama di Pengadilan Negeri Bandung - Mardius, Mardius; Putra, Wiwin; Supeno, Supeno (Wajah Hukum, 2024)
Marriage cannot be separated from the religious aspect, especially when Law No.1 of 1974 concerning Marriage emphasizes the importance of the religious aspect in the conditions for the validity of a marriage as regulated in Article 2 paragraph (1) "Marriage is valid, if it is carried out according to the laws of each religion and his beliefs", confirmed by MUI fatwa Number 4/MUNAS/VII/- MUI/8/2005 that Muslim women are prohibited from marrying non-Muslim men or Muslim men are prohibited from marrying women from people of the Book, in the Bandung District Court Decision. Number: 87/Pdt.G/2020/PN.Bdg, there was a divorce case that was caused by one of the parties changing religion. The formulation of the problem discussed in this thesis is: 1. Judge's Considerations in Deciding Divorce Case No.87/Pdt.G/2020 PN.Bdg which was caused by one of the spouses changing religion at the Bandung District Court and the legal consequences of divorce caused by one of the spouses Changing Religion in Bandung District Court. The research method used is a normative juridical method, namely research based on the study of documents which can be in the form of books or other literature, especially in this research, namely the Bandung District Court Decision Number: 87/Pdt.G/2020/PN.Bdg. From the results of the research, the judge's considerations regarding divorce in case No.87/Pdt.G/2020 PN.Bdg which was caused by one of the spouses changing religion at the Bandung District Court, is in the case where the plaintiff has converted to Islam and insists on filing for divorce on the grounds of his new religion. not allowed. In accordance with the Fatwa of the Indonesian Ulema Council Number 4/MUNAS VII/MUI/8/2005 concerning interfaith marriages, it is stipulated that interfaith marriages are haram and invalid. In addition, disputes, quarrels and quarrels often occur continuously due to differences of opinion and belief, which result in the division of joint assets, maintenance and maintenance for the survival of their children, regarding child custody (hadhanah) and the settlement of marital assets. resolved separately from the divorce suit he filed.